(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
This paper delves into often-unspoken realms of human suffering – tragedy and psychosis – to uncover the role that art can play in understanding and overcoming experiences that defy conventional language. Dovetailing from Heidegger’s aesthetics, I explore the unique qualities that make the artistic process such a powerful medium for existential restoration, connecting otherwise disparate individuals to the wider tapestry of humanity. Ultimately, I argue for a new understanding of ’artistic literacy,’ emphasising the benefits that unconventional modes of expression hold for the expresser, listener and humanity at large.